AB0758 Extra corporal membrane oxygenation in an adolescent with anca associated vasculitis. (23rd January 2014) - Downie, J.; Cruikshank, M.; McGettrick, A.; Perry, N.; Kidson, C.; Davies, P.; Hughes, D.; Davidson, J.
Abstract : Background: Hypoxaemic respiratory failure secondary to diffuse alveolar haemorrhage is rare in children but can be life threatening. A rare cause is "Anti-neutrophil cytoplasmic antibody associated vasculitis" (AAV). Conventional ventilation may not provide sufficient support and extra corporeal membrane oxygenation (ECMO) may be required. Coordinating extracorporeal supports with the medical management of AAV can be challenging. Objectives: We describe a 15-year-old girl successfully treated for AAV affecting the upper and lower respiratory tract and renal system, who required ECMO, plasma exchange and renal replacement therapy. Methods: A previously well, 15 year old smoker, presented to her GP with a 3 year history of self induced vomiting. Investigations identified renal failure, precipitating local hospital referral. Over the following 4 days, she became anuric and developed pulmonary oedema requiring transfer to the tertiary hospital. Further clinical deterioration resulted in a requirement for ventilation and haemodialysis. In the hours following her initial haemodialysis she had a large pulmonary haemorrhage. Her lung function deteriorated further and she required ECMO support. She received ECMO for 7 days, high frequency oscillatory ventilation for 4 days then conventional ventilation for further 46 days. A tracheotomy was performed to aid long term ventilation. Results: Immunological investigations confirmed markedly raised myeloperoxidase (MPO)antibodies (317 U/ml). Renal biopsy subsequently showed severe damaged kidney with near total glomerular obliteration and evidence to suggest recent crescentic glomerulonephritis. Microlaryngobronchoscopy (MLB) confirmed extensive subglottic granulomata. A diagnosis of AAV was made. Her immunosupressive regimen consisted of high dose steroids, plasma exchange, intravenous cyclophosphamide and rituximab. Her MPO antibody titres fell steadily, returning to normal (4.5U/ml) after 10 months. Her latest pulmonary function tests are normal. A repeat MLB showed resolution of the subglottic granulomata and her tracheostomy tube has been removed. She is currently well at home, but requires haemodialysis four times a week. She remains on oral prednisolone and mycophenolate mofetil. Conclusions: Acute rheumatological illness can necessitate the need for invasive life saving support. Life threatening pulmonary haemorrhage is not a contraindication for the use of ECMO support despite the associated need for anticoagulation. ECMO may allow time to establish a diagnosis, tailor a specific management strategy and assess the cumulative disease burden. Our case demonstrates the successful use of three simultaneous extracorporeal circuits – ECMO, continuous veno-venous haemofiltration and plasma exchange. The additional complexities that extracorporeal supports impart upon the specific disease management requires continual re-evaluation. There is need for good intensive care and multi specialist support if prognosis from these challenging patients is to continue to improve. Disclosure of Interest: None Declared